X-ray scattering from semiconductors - Fewster, Paul F. (Imperial College Press, 2000)
This text provides a description of the techniques involved in obtaining that information, including X-ray diffractometers and their associated instrument functions, data collection methods, and the simulation of the diffraction patterns observed. Also presented are examples and procedures for interpreting the data to build a picture of the sample, much of which is common to materials other than semiconductors.